An Analytical Study for Market Integration Hypothesis for Natural Rubber Cultivation of Kerala
The purpose of this article is to analyse the market integration and causal nexus between two market prices of rubber in Kerala Economy during the period of pre and post reform. Augmented Dickey Fuller (ADF) test is used ascertains that the variables are exact order of integration. Cointegration technique used to examine the validity of the market integration hypothesis with reference to prices of rubber in Kerala. After cointegration test, Error Correction Model (ECM) used to identify the that market prices of peripheral price on main market price and vice versa. The analysis shows that a strong evidence of an existence of market integration in Rubber price during the post reform period. More over, the price changes of rubber will be transmitted from peripheral to main market and vice versa during the reform period.